Postprison relationship dissolution and intimate partner violence: Separation-instigated violence or violence-instigated separation?. Issue 5 (4th July 2018) - McKay, Tasseli E.; Lindquist, Christine H.; Landwehr, Justin; Ramirez, Derek; Bir, Anupa
Abstract: Prior work suggests that partner violence may occur in the context of relationship dissolution among couples in which the male partner is reentering from prison. Using longitudinal data from 666 reentering men and their female partners, we found that couples who were no longer romantically involved were more likely to report violence in the relationship at reentry than those who were. Among those who broke up, 28% of women and 10% of men reported violence as a reason. Men who reported IPV in their relationships were less likely to report being in a romantic relationship with their study partner at the next survey wave than those who did not.